Electric Drive Discrete Control System with Automatic Switching-On Reserve for Autonomous Settlement - Tsytovich L.I.; Brylina O.G.; Nesterov A.S.,; Tyugaev A.V; Loginova N.A; Lopukhova E.A. (Problems of the Regional Energetics, 2015)
The paper aims at developing of control the water supply system’s electric drives for autonomous settlement. The system provides automatic switching to a reserve control channel at refusal of any of the functional elements of the working regulation channel. Usually, such systems have a test signal generator and analyzer to system response to their impact. This result to an increase in the structural redundancy of the system, increase its cost and increase the requirements for the staff qualification. A specific feature of the system is its ability to self-diagnosis of catastrophic malfunctions of scheme’s components and an automatic switching-on the reserve control channels, without applying any test signals to the whole complex of electrical equipment. Multi-zone integrating regulator with frequency-pulse-width modulation realizes this technical solution. Control system structure and signals timing diagrams are presented. The construction principle of adaptive interval-code synchronization device with improved noise stability to control the voltage regulators serving for smooth start-up of asynchronous motors of water pumps is considered as well. Such solution allowing increase noise stability and reliability work of the system in conditions of limited power electrical networks, which is characteristic for the autonomous settlements. The article may be of interest to specialists in the field of power electronics and information electronics, electric drives and process automation.